Quantification of volatile flavor compounds in off-flavor and commercial reduced-fat milk samples - Francis, L.L.; Lee, J.; Chambers, Delores H.; Jeon, I.J.; Simmons, S.R.; Schmidt, Karen A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Various chemical compounds contribute to the naturally pleasant flavor of milk. Over time, however, and with unwanted chemical reactions, loss of flavor is inevitable. This study was conducted to identify and quantify volatile flavor compounds associated with off-flavored and commercial reduced-fat milk products. Fresh milk was used for the preparation of altered milk samples having off-flavors such as “light-oxidized” and “high-acid.” Milk lacking freshness (i.e., milk produced two weeks before sampling and maintained at 40oF in the dark) also was compared with fresh unaltered milk and two commercial milk samples. For headspace analysis, milk samples were subjected to SPME-GC for volatile compound identification. In addition, the composition and aerobic and coliform microbial counts for all milk samples were analyzed. The milk samples did not differ in the concentrations of volatile flavor constituents. When comparing “light-oxidized” milk samples (200 lx exposure for 1 or 3 hr), 2-butanone and pentanal concentrations tended to increase as light exposure time increased. All milk samples had similar fat and total solids contents. “High-acid” milk had a greater total aerobic microbe count than the other milk samples. Fresh milk had a greater octanal concentration than the offflavored reduced-fat milk samples did. This might indicate that octanal is an important contributor to fresh milk flavor and deserves further study.
Keywords: Dairy; Milk; Flavor; Compounds; GC Analysis